Identification of Novel Immune Ferropotosis-Related Genes Associated With Clinical and Prognostic Features in Gastric Cancer - Xiao, Chen; Dong, Tao; Yang, Linhui; Jin, Liangzi; Lin, Weiguo; Zhang, Faqin; Han, Yuanyuan; Huang, Zhijian (Frontiers in Oncology, 2022)
Background: Gastric cancer (GC) is the fifth most common cancer and the third most common cause of cancer death in the world. At present, the rapid development of tumor immunology and ferropotosis has brought new directions for the treatment of gastric cancer. Therefore, it is urgent to find potential targets and prognostic biomarkers for immunotherapy combined with ferropotosis. Methods: By mining TCGA, immune-related genes, ferropotosis-related genes and immune-ferropotosis-related differentially expressed genes (IFR-DEGs) were identified. The independent prognostic value of IFR-DEGs was determined by differential expression analysis, prognostic analysis, and univariate and lasso regression analysis. Then, based on the prognostic risk model, the correlation between IFR-DEGs and immune scores, immune checkpoints were evaluated. In addition, we predicted the response of high and low risk groups to drugs. Results: A 15-gene prognostic feature was constructed. Compared with the low-risk group, the high-risk group had a poor prognosis. The level of Treg immune cell infiltration in the high-risk group was higher than that in the low-risk group, and the tumor purity, immune checkpoint PD-1 and CTLA4, and immunity in the high-risk group were higher than those in the low-risk group. These results indicate that immune ferropotosis-related genes may be potential predictors of STAD's response to ICI immunotherapy biomarkers. In addition, the response of small molecule drugs such as Nilotini, Sunitinib, Imatinib, etc. for high and low risk groups was predicted. Conclusion: IFRSig can be considered as an independent prognostic feature and may be able to estimate OS and clinical treatment response in patients with STAD. This study provides a new understanding of the IF gene during the occurrence and development of STAD.